THE INFLUENCE OF WORK STRESS AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT INDOMARET, TANAH BARU BRANCH, DEPOK - Muhamad Guruh; Fitri Sabina; Surya Budiman (International Journal Management and Economic, 2025)
This study aims to analyze the impact of work stress and work motivation on employee performance at the Indomaret Tanah Baru branch in Depok. The study uses a quantitative approach with a survey method involving 60 respondents. The work stress variable is measured through workload, work conflict, work hours, work environment, and career opportunities, while work motivation includes physiological needs, security, sense of belonging, self-esteem, and self-actualization. Employee performance is measured through job knowledge, work outcomes, mental agility, initiative, attitude, and time discipline. The analysis results indicate that work stress significantly affects employee performance. Work motivation also has a significant impact on employee performance. Simultaneously, work stress and work motivation together have an impact on employee performance, showing that 84.6% of the variability in employee performance is influenced by these two variables. The study concludes that good management of work stress and appropriate work motivation can improve employee performance. It is recommended that Indomaret enhance its stress management system and provide relevant motivation to increase employee productivity and efficiency.